From analog to digital: Digitization and digital preservation of microfilm collections - Adeline, Intania; Damayani, Ninis Agustini; Silvana, Tine (Faculty of Communication, Padjadjaran University, 2025)
Background: The advancement of information technology has transformed the management of microfilm collections through digitization. This process aims to align with the increasingly digital information consumption patterns of society, while also preserving information and enhancing accessibility.Purpose: This study explores the stages of microfilm digitization, the challenges encountered, and applicable digital preservation strategies to ensure the longevity of information.Methods: Conducted using a qualitative descriptive approach, the research collected primary data through direct observation of the digitization process and secondary data from literature review. The data were analyzed by identifying, categorizing, and explaining key elements such as digitization activities, challenges, solutions, and preservation strategies. Results: The findings indicate that microfilm digitization consists of three stages: pre-transformation (administrative and equipment preparation), transformation (microfilm scanning), and post-transformation (quality control and file management). Challenges include the dependency of digital output quality on the condition of the microfilm, limited human and financial resources, and the difficulty of sustaining digital access amid technological changes. Solutions include the use of artificial intelligence to improve OCR accuracy and automate metadata analysis. To ensure long-term access, preservation strategies such as data refreshing, format migration, and digital environment emulation are essential. With these strategies, information institutions can safeguard knowledge and reinforce the role of libraries in the digital era.